Mesmerized : how Ben Franklin solved a mystery that baffled all of France - Rockliff, Mara; Bruno, Iacopo (Somerville, Massachusetts : Candlewick Press, 2015)
Discover how, in Paris in the 1770s, Benjamin Franklin's scientific method challenged a certain Dr. Mesmer's mysterious powers in a whimsical look at a true moment in history.--
Includes bibliographical references (page 45)
Junior Library Guild selection
Keywords: Franklin, Benjamin, -- 1706-1790 -- Juvenile literature; Mesmer, Franz Anton, -- 1734-1815 -- Juvenile literature; Franklin, Benjamin, -- 1706-1790; Mesmer, Franz Anton, -- 1734-1815.; Science -- Methodology -- Juvenile literature; Psychology -- Experiments -- Juvenile literature; Mesmerism -- Juvenile literature; Science -- Experiments -- Juvenile literature; Science -- Methodology; Psychology -- Experiments; Mesmerism; France -- History -- 18th century -- Juvenile literature; France -- History -- 18th century